Personal Branding Content Creator di Media Sosial Tiktok - Muhammad Dimas Chandra Purnama Dimas; Kiki Zakiah (UNISBA Press, 2023)
Abstract. Branding is often known as the activities carried out by companies in introducing their products. As the Times develop, branding is no longer only done by companies but can also be done by individuals or commonly called Personal Branding. Personal branding can be done by anyone, one of which is done by content creators. Content creators use Tiktok social media as a medium to build and shape personal branding. Personal branding is a strong and clear image that exists in the mind of someone about yourself, the three important aspects of personal brand is your own, promises and relationships. Researchers use qualitative research methods with a case study approach. Researchers collect, process, and systematically analyze factual data about Tiktok content creator Personal Branding obtained from Alwi fahry, so that they can draw conclusions that are relevant to Alwi fahry's Personal Branding, by conducting interviews, observations, and literature studies. From the results of research that has been done, the researchers obtained a form of personal branding conducted by Alwi fahry in self-branding conducted. Among them are personal branding, the meaning of personal branding, and the use of Tiktok in building personal branding. Abstrak. Branding sering kali dikenal sebagai kegiatan yang dilakukan perusahaan dalam mengenalkan produknya. Seiring berkembangnya zaman, branding tidak lagi hanya dilakukan oleh perusahaan saja melainkan bisa juga dilakukan oleh perorangan atau biasa disebut dengan Personal Branding. Personal branding dapat dilakukan oleh siapapun, salah satunya dilakukan oleh content creator. Content creator memanfaatkan media sosial Tiktok sebagai media untuk membangun dan membentuk personal branding. Personal branding adalah image yang kuat dan jelas yang ada di benak seseorang mengenai diri sendiri, tiga aspek penting personal brand tersebut adalah anda sendiri, janji dan hubungan. Peneliti menggunakan metode penelitian kualitatif dengan pendekatan studi kasus. Peneliti mengumpulkan, mengolah, dan menganalisis secara sistematis data faktual mengenai Personal Branding content creator Tiktok yang diperoleh dari Alwi fahry, sehingga dapat mengambil kesimpulan yang relevan dengan Personal Branding yang dilakukan Alwi fahry, dengan cara melakukan wawancara, observasi, dan studi kepustakaan. Dari hasil penelitian yang telah dilakukan, maka peneliti memperoleh bentuk personal branding yang dilakukan oleh Alwi fahry dalam branding diri yang dilakukan. Di antaranya adalah personal branding yang dilakukan, makna personal branding, dan penggunaan Tiktok dalam membangun personal branding.